Ekonomi ve Kaos Teorisi - Kesici, Sinan (İstanbul Kültür Üniversitesi Yayınları, 2006)
Kaos teorisinin ekonomistler tarafından bilinmesi, ekonomideki dengenin zorlununun da anlaşılmasına neden olmuştur. Ekonomideki karmaşık piyasa faaliyetleri nedeniyle bu faaliyetleri nedeniyle bu faaliyetleri modellemek birçok güçlükler içermektedir. Kaos teorisinin ekonomideki uygulamaları bu güçlüklerin aşılması amaçlıldır. Nash dengesi yaklaşımı da karşılaşılan güçlüklerin aşılmasını içerir. Temeldeki sorun ise dinamiklerde kaos varlığının olup olmadığıdır. Bu sorunun yanıtı ancak genel denge modelinin temel tanımları ile verilebilir. Ancak genel denge teorisindeki varsayımlardan sadece varlık sorunu çözülebilmişken kararlılık sorunu halen mevcuttur. Sosyal bilimlerdeki metodoloji, sonuçların deneyselden çok tarihsel verilerden çıkarılmasını gerektirir. Ekonomide, geçmiş ile ilgili açıklamalarda işe yarayan fakat, philips eğrisi gibi, tahminsel alanda başarısız olmuş bir çok örnekler olmuştur.

Knowing of the chaos theory by the economists has caused the understanding of the dificulties due to the complex marketing facilities in economy. The applications of the chaos theoery related to economy have aimed to overcome these difficulties. Nach equilibrium approcah concerns the overcoming of the difficulties too. The fundamental problem is the existence of the chaos in these dynamics or not. The answer of the question can only be given trough the main definitions of the general equilibrdium model. Nevertheless, of the hypotheses in general equilibrium theory, only the existence problem is solved while the stability problem is still existing. The methodology in social sciences necessitates the emerging of the results from the historical data rather than the experimental ones. In economy, the explanations related to the past are fruitful but, like Phillips curve, there are lost of unsuccessful samples in the expectational field.
Keywords: ekonomi ve kaos; karmaşık sistemler; non-lineer dinamikler; Economy and chaos; complicity systems; non-linear dynamics